2020
DOI: 10.2147/ijgm.s273900
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Predictors of Thyroid Dysfunction Among Type 2 Diabetic Patients: A Case–Control Study</p>

Abstract: Background: Type 2 diabetes mellitus (T2DM) and thyroid disorders are common endocrine disorders. This case-control study aims to determine the prevalence and predictors of thyroid disorders in T2DM patients. Methods: A total of 998 T2DM patients attending a tertiary hospital were included and underwent investigations for thyroid function: thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3); and glycated hemoglobin (HbA1c). They were compared with 343 non-diabetic subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 60 publications
9
34
0
Order By: Relevance
“…In this study, lower levels of thyroid hormones and a higher prevalence of TD were found in patients with diabetes as compared to the control group, which is in accordance with previous studies [10,11]. The prevalence of TD varied in patients with DM in different regions, ranging from 4% to over 20% [2].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, lower levels of thyroid hormones and a higher prevalence of TD were found in patients with diabetes as compared to the control group, which is in accordance with previous studies [10,11]. The prevalence of TD varied in patients with DM in different regions, ranging from 4% to over 20% [2].…”
Section: Discussionsupporting
confidence: 91%
“…This reflects the poor glycaemic status of most diabetic patients in our environment as more than half of the T2DM patients in this study did not achieve the glycaemic goal, which is concordant with the pattern in earlier studies conducted in Jordan. [61][62][63][64] This can be explained as the majority of our patients did not follow a diabetic diet plan, were physically inactive, and their high BMIs. Besides, financial constraints may be one of the major contributing factors in Jordan.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Khassawneh et al reported no significant associations between thyroid disorders and complications or duration of diabetes (p>0.050) [14].…”
Section: These Results Came In Agreement Withmentioning
confidence: 91%